Ocena skuteczności i efektywności działań promocyjnych na przykładzie reklamy - Dudek-Frysiak, Honorata (Evaluation Effectiveness and Efficiency of Promotion-Mix on Example of Advertisement, 2005)
In present enterprises management knows, that promotion is necessary to reaching success on the market. The point that should draw special attentions is estimation results of promotions. The base of every decision connected with promotion mix, should be analysis of efficiency and efficacy. The article above, is review method of evaluation efficiency and efficacy
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 70-79